Enhanced Recovery Implementation and Perioperative Outcomes in Posterior Fusion Patients. Issue 16 (15th August 2020) - Fiasconaro, Megan; Wilson, Lauren A.; Bekeris, Janis; Liu, Jiabin; Poeran, Jashvant; Soffin, Ellen M.; Memtsoudis, Stavros G.
Abstract : Study Design: Retrospective cohort study. Objective: We sought to determine if there was an association between enhanced recovery after surgery (ERAS) implementation level and complication risk, length of stay, and cost of hospitalization. Summary of Background Data: ERAS protocols aim to minimize the stress response of surgery by promoting early mobilization, oral intake, as well as improvement of analgesia. Implementation of ERAS protocols in spine surgeries has been limited to mostly single-institution studies, and no population-based data exist on the impact of the level of implementation of various ERAS components on outcomes. Methods: In this study we identified 265, 576 posterior lumbar fusion surgeries from 2006 to 2016. The main effect was the application of eight ERAS-related practices: (1) multimodal analgesia, (2) tranexamic acid, (3) antiemetics, (4) steroids, (5) early physical therapy, (6) avoidance of urinary catheters, (7) avoidance of patient-controlled analgesia, (8) avoidance of wound drains. Patients were classified by levels of ERAS implementation: "High, " "Medium, " and "Low" ERAS implementation if they received more than five, three to five, or less than three ERAS components, respectively. Mixed-effects models measured associations between ERAS implementation categories and complications, length and cost of hospitalization; odds ratios (OR, or average ratios for continuous outcomes), and 99.4% confidence intervals (CI) were reported. Results: Overall, 13.3%, 62.8%, and 24.4% of cases were categorized as "High, " "Medium, " and "Low" ERAS implementation, respectively. After adjusting for study variables, "Medium" and "High" (compared with "Low") ERAS implementation levels were significantly associated with incrementally improved outcomes regarding "any complication" (OR 0.84 CI 0.80–0.88 and OR 0.77 CI 0.71–0.84), cardiopulmonary complications (OR 0.75 CI 0.68–0.73 and OR 0.69 CI 0.59–0.80), length of stay (average ratio 0. 94 CI 0.93–0.94 and average ratio 0.91 CI 0.90–0.91), and hospitalization cost (average ratio 0.99 CI 0.98–0.99 and average ratio OR 0.95 0.95–0.96). Conclusion: In a cohort undergoing posterior lumbar spine fusion the level of utilization of ERAS protocol components was independently associated with incrementally improved complication odds as well as reduced length of stay and a small decrease in overall hospitalization cost. Level of Evidence: 3 Abstract : Implementation of enhanced recovery after surgery (ERAS) protocols in spine surgeries has not been well-studied. This retrospective cohort study identified posterior lumbar fusion surgeries (2006–2016), and mixed-effects models measured associations between ERAS implementation and complications, length, and cost of hospitalization. ERAS utilization level was associated with improved complication odds, reduced length of stay (LOS) and hospitalization cost.